Debate over Islamic Symbolism and Substantialism in the Formulation of Local Regulation in Tasikmalaya Municipality - Yuliawati, Fitriyani; Nurohman, Taufik (Jurnal Politik Indonesia: Indonesian Political Science Review, 2018)
This study aims to reveal debate over the formulation of local regulation. Particularly, it seeks to know political dynamics at the grassroot level in policy-making. Theoretical assumption mentions that policy-making is not only a process of government technocracy, but it can also a debate over current discourse among citizens. The qualitative study discloses that the political debate over this discourse occurs due to contradictory perspectives on the aspirations of Shari’a law as a part of formal institutions in the state. The first camp argued that Islam should exist in the public as an effort to build an ideal society. Islam must be included as part of the state, at least in local regulation. In contrast, the second camp argued that in building the ideal society, state does not need to include Islam as part of the state in the regulation.